Water marketing in California - Easton, James L., author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 1989)
Few things have been talked about more and done less in California than water marketing. It's interesting that in one of the world's consummate entrepreneurial environments, a commodity as vital as water is so difficult to buy and sell. Why has water marketing become widely used in the rest of the southwestern United States and even in the Midwest and not in California? The answer to that question is complex. The discussion of water marketing will be divided to treat surface and subsurface water separately.
USCID regional meetings -- 1989
Not digitized by CSUL Digital Services.
Presented at Planning for water shortages: water reallocations and transfers drought management: proceedings from the 1989 regional meetings held on August 24-25, 1989 in Boise, Idaho and on October 19-21, 1989 in St. Louis, Missouri.